2013
DOI: 10.1068/i0517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Visual Stimuli on Temporal Order Judgments of a Sequence of Pure Tones

Abstract: We investigated what effect visual spatial information had on auditory temporal order judgments (TOJs) and examined what effect visual stimuli had on the TOJs of sequences of pure tones in experiment 1. The auditory stimuli were sequences of four distinct pure tones. The visual stimuli consisted of two vertically aligned flashes: one flashed before the first tone and the other flashed after the last tone. Participants judged whether the temporal order of the second and third tones in auditory stimuli occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Leone and McCourt ( 2013 ) revealed a new aspect of facilitative audiovisual integration that disagrees with the well-known idea of inverse effectiveness. Tanabe and Iwaki ( 2013 ) found perceptual effects of visual spatial information on auditory temporal order judgments and simultaneity judgments. Speech-oriented research by Spector and Maurer ( 2013 ) suggested naturally biased correspondences between vowel sound and shape, investigating the influence of vowels on sound–shape matching in toddlers.…”
mentioning
confidence: 99%
“…Leone and McCourt ( 2013 ) revealed a new aspect of facilitative audiovisual integration that disagrees with the well-known idea of inverse effectiveness. Tanabe and Iwaki ( 2013 ) found perceptual effects of visual spatial information on auditory temporal order judgments and simultaneity judgments. Speech-oriented research by Spector and Maurer ( 2013 ) suggested naturally biased correspondences between vowel sound and shape, investigating the influence of vowels on sound–shape matching in toddlers.…”
mentioning
confidence: 99%